1993
DOI: 10.1177/004728759303100305
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of State Traveler Information Centers on Tourist Length of Stay and Expenditures

Abstract: This article reports on a 1987 study of the effect of travel information centers (TIC) in Colorado. Stopping at the TIC resulted in a 2.2 day average increase in length of stay and an estimated $1,026,000 additional spending. The income groups most affected were middle and high income level groups. Most travelers who stopped did so to get information — a finding in contrast to earlier studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 2 publications
0
30
0
1
Order By: Relevance
“…Tourism authorities have regarded TICs as the most important element in tourism promotion, encouraging tourists to stay for a longer period of time and spend more money within their territories (Fesenmaier, Vogt, & Stewart, 1993;Tierney, 1993). Ballantyne, Hughes, and Ritchie (2009) indicated that TICs contribute significantly to the socio-economic and recreational well-being of particular communities by facilitating tourists to experience local attractions and events, and to financially support local retails, accommodations, and restaurants.…”
Section: Tourist Information Centers (Tics)mentioning
confidence: 99%
See 1 more Smart Citation
“…Tourism authorities have regarded TICs as the most important element in tourism promotion, encouraging tourists to stay for a longer period of time and spend more money within their territories (Fesenmaier, Vogt, & Stewart, 1993;Tierney, 1993). Ballantyne, Hughes, and Ritchie (2009) indicated that TICs contribute significantly to the socio-economic and recreational well-being of particular communities by facilitating tourists to experience local attractions and events, and to financially support local retails, accommodations, and restaurants.…”
Section: Tourist Information Centers (Tics)mentioning
confidence: 99%
“…Accordingly, those studies on the chief engines of tourism promotion focused on limited topics: behavioral differences between TIC visitor and non-visitor groups (e.g., Howard & Gitelson, 1989;Stewart et al, 1993), tourist motivations for visiting the facilities (e.g., Fesenmaier, 1994;Gitelson & Perdue, 1987), and TIC site preferences (e.g., Pennington-Gray & Vogt, 2003;Perdue, 1995). While a couple of studies (e.g., Tierney, 1993) attempted to utilize an economic approach, concentrating on the impacts of TIC development and services on tourist expenditures, there is no comprehensive research available on tourist demand for TIC visits.…”
Section: Tourist Information Centers (Tics)mentioning
confidence: 99%
“…Finally, travel guidebooks, travel or automotive clubs and local tourist offices (Andereck et al, 2003;Fesenmaier & Vogt, 1993;Tierney, 1993) were also perceived as valuable information sources to consumers when they sought for travel related information. However, the effectiveness of these three sources was still uncertain, particularly when used to select a travel agency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The effectiveness of some of these promotional methods has been researched while others have received little attention. Researchers have specifically considered the influence of advertising (Butterfield, Deal, & Kubursi, 1998); information fulfillment programs (Johnson & Messmer, 1997;Messmer & Johnson, 1993); highway welcome centers (Fesenmaier & Vogt, 1993;Tierney, 1993); the Internet (Tierney, 2000); and brochures (Zhou, 1997).…”
Section: Use Of Information Sourcesmentioning
confidence: 99%
“…Quite a number of studies have been conducted looking at the effectiveness of welcome centers or other tourism information centers. The effectiveness of information centers on tourist expenditures is still uncertain, but there is some evidence that centers result in longer stays and there is strong evidence that they influence travelers' tourism product choices (Fesenmaier & Vogt, 1993;Tierney, 1993). Most recently, the Internet has emerged as an information source.…”
Section: Use Of Information Sourcesmentioning
confidence: 99%